Effectiveness of Moringa (Moringa olifera) Leaf Flour in Feed on Growth and Survival of Vaname Shrimp (Litopenaeus vannamei) - Scolastika Tanggel; Yudiana Jasmanindar; Wesly Pasaribu (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Vaname shrimp is Indonesia's leading product in national and international markets. Moringa leaves are a source of vegetable protein that is used as an additional ingredient in vaname shrimp feed. This study aims to determine the effectiveness of moringa leaf meal in feed on the growth and survival of vaname shrimp. This study consisted of four treatments with three replicates each, namely: A (control) without moringa leaf meal, B (added moringa leaf meal by 10%), C (added moringa leaf meal by 15%), and D (added moringa leaf meal by 20%). Vaname shrimp weighing 0.008-0.009 g each were reared in aquariums measuring 40×30×30 cm with a stocking density of 10 shrimp/aquarium. Shrimp were kept for 60 days and fed with moringa leaf meal and without moringa leaf meal. The results showed that the addition of moringa flour in vaname shrimp feed by 20% (treatment D) produced the highest absolute growth of 1.34 g with a specific growth rate of 0.022 g%/day.